Animal osmoregulation - Bradley, Timothy J. (Oxford : Oxford University Press, 2009)
Osmoregulation and water balance are essential topics in animal physiology. This book starts with the physical properties of water, and the influence that it has on biological design. It then looks at the effect of the environment on physiology.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Osmoregulation